The implementation of teledentistry training in orthodontic practice: an explanatory sequential mixed-methods study - Supakit Peanchitlertkajorn; Charn Ngamdachakij; Boonsita Wongwatjana; Wichayaporn Jongpatranichpunth; Kawin Sipiyaruk (BMC Medical Education)
Abstract Background Teledentistry has been increasingly used in orthodontic practice. Comprehensive and appropriate trainings should be required to enhance the effective use of teledentistry. However, there is still a lack of adequate teledentistry training in postgraduate orthodontic programs. Therefore, this research aimed to investigate the perceptions of key stakeholders regarding the necessity of teledentistry and to formulate a conceptual framework highlighting the implementation of teledentistry training in orthodontic education. Methods This research employed an explanatory sequential mixed-method design. The research participants included orthodontic instructors, practitioners, and residents from the Faculty of Dentistry, Mahidol University. The participants were asked to complete an online questionnaire to provide initial overview of this topic. They were then purposively selected and recruited for a semi-structured interview, allowing the exploration of in-depth information. Results Participants expressed positive perceptions toward the use of teledentistry in orthodontic practice. The conceptual framework derived from this study highlighted awareness of both advantages and concerns of teledentistry among participants, leading to the necessity of training in orthodontic education. The findings also provided in-depth information regarding expected learning outcomes, a combination of training delivery and assessment strategies to adequately prepare learners for the use of teledentistry in orthodontic practice. Conclusion This study supports the implementation of teledentistry into orthodontic practice, with participants recognizing both its benefits and concerns. Emphasizing the significance of incorporating teledentistry preparation into orthodontic curricula, it is essential to outline expected learning outcomes, delivery methods, and assessment strategies for effective training.